Randomized, Double-Blind, Crossover Trial of Amitriptyline for Analgesia in Painful HIV-Associated Sensory Neuropathy - Dinat, Natalya (PLoS One, 2015)
We conducted a randomized, double-blind, placebo-controlled, crossover study at a single center in South Africa, to ascertain whether amitriptyline is an effective analgesic for painful HIV-associated sensory neuropathy of moderate to severe intensity in: i) antiretroviral drug naive individuals, and ii) antiretroviral drug users. 124 HIV-infected participants (antiretroviral drug naive = 62, antiretroviral drug users = 62) who met the study criteria for painful HIV-associated sensory neuropathy were randomized to once-daily oral amitriptyline (titrated to a median: interquartile range of 50: 25-50 mg) or placebo for six weeks, followed by a three-week washout period and subsequent treatment crossover. The primary outcome measure was change from baseline in worst pain intensity of the feet (measured by participant self-report using an 11-point numerical pain rating scale) after six weeks of treatment. 122 of 124 participants completed all study visits and were included in the analysis of the primary outcome. In the antiretroviral drug-naive group (n = 61) there was no significant difference in the mean change in pain score from baseline after six weeks of treatment with placebo or amitriptyline [amitriptyline: 2.8 (SD 3.3) vs. placebo: 2.8 (3.4)]. Similarly, there was no significant difference in the change in pain score after six weeks of treatment with placebo or amitriptyline in the antiretroviral drug-user group (n = 61) [amitriptyline: 2.7 (3.3) vs. placebo: 2.1 (2.8)]. Controlling for period effects and treatment order effects did not alter the outcome of the analyses. Nor did analyzing the intention-to-treat cohort (missing data interpolated using baseline observation carried forward) alter the outcome of the analyses. In summary, amitriptyline, at the doses used here, was no more effective than an inactive placebo at reducing pain intensity in individuals with painful HIV-associated sensory neuropathy of moderate to severe intensity, irrespective of whether they were on antiretroviral therapy or not. TRIAL REGISTRATION: ISRCTN 54452526